2005
DOI: 10.1111/j.1440-1746.2005.03895.x
|View full text |Cite
|
Sign up to set email alerts
|

Small carcinoma of the pancreas is curable: New computed tomography finding, pathological study and postoperative results from a single institute

Abstract: The presence of s-PC qualifies as early PC and has a good prognosis. The CT black + white sign will be useful in the diagnosis of s-PC accompanying pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 16 publications
0
37
0
4
Order By: Relevance
“…Because patients generally present with symptoms relating to late stages of the disease, diagnosis of resectable PDAC is achieved in less than 15% of cases (1). However, investigators have reported that diagnosis and resection of early-stage PDAC (<2 cm in size) can result in a 4-y survival rate of up to 78% (2)(3)(4)(5). These data suggest that early detection of PDAC can improve patient outcome.…”
mentioning
confidence: 96%
“…Because patients generally present with symptoms relating to late stages of the disease, diagnosis of resectable PDAC is achieved in less than 15% of cases (1). However, investigators have reported that diagnosis and resection of early-stage PDAC (<2 cm in size) can result in a 4-y survival rate of up to 78% (2)(3)(4)(5). These data suggest that early detection of PDAC can improve patient outcome.…”
mentioning
confidence: 96%
“…Unlike large pancreatic cancer which is usually symptomatic, small cancers are generally asymptomatic or have non-specific symptoms. In a recent series of small pancreatic cancer 50% of patients were diagnosed incidentally on crosssectional imaging (10). Extra-pancreatic spread is frequently present in small pancreatic cancer.…”
Section: Progression Of Pancreatic Cancer From Pre-invasive Precursormentioning
confidence: 99%
“…To put this in perspective, the median size of resected pancreatic cancers is 30 mm (6). Small cancers constitute only ~ 20% of resected pancreatic cancers (10). In an unpublished series of 300 patients with pancreatic ductal adenocarcinomas who underwent margin-negative (R0) resection between 1987 and 2000 at our center, 54 (18%) were small (i.e., ≤20mm).…”
Section: Definition(s) Of Early Pancreatic Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Resection of small tumors (< 2 cm or T1) improves 5-years survival (30% to 60%) [9,10] . However it has been alluded that the better prognosis is for tumors < 1 cm (T1a) with 5-years survival up to 78% [6,11,12] .…”
Section: Introductionmentioning
confidence: 99%